The relationship between complete blood count parameters with thyroid stimulating hormone levels in pregnant women - Neda Sharifi; Atefe Ebrahimiyan; Fariba Mardani; Saeed Erfanpoor; Rasoul Rahmani (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2022)
Introduction: Iron deficiency anemia reduces the activity of thyroperoxidase and thus inhibits the production of thyroid hormone. Therefore, this study was performed with aim to determine the relationship between complete blood count parameters with the level of thyroid stimulating hormone in pregnant women.Methods: This descriptive-analytical cross-sectional study was performed in 2018 on 130 pregnant women who had referred to community health centers covered by Gonabad University of Medical Sciences for first prenatal care. Data were collected at maternal referral, using a checklist containing demographic information of maternity (maternal age, education, occupation, gestational age, etc.) and first trimester pregnancy test results. Data were analyzed by SPSS software (version 16) and Kolmogorov-Smirnov, Spearman correlation and Pearson correlation tests. P<0.05 was considered statistically significant.Results: Mean TSH of women was 1.95± 1.24 mlu/l and mean total Hb was 12.81±1.08 g/dl and mean total MCHC was 23.89±1.34 g/dl. In multivariate model, none of the variables had a significant statistical relationship with TSH and only the MCHC variable had a significant relationship with TSH (P = 0.041).Conclusion: The MCHC variable had a significant relationship with TSH, but the other blood parameters had no significant relationship with TSH level. It is recommended that further studies be performed in the future to determine the relationship between these two variables.